Adherence to antihypertensive drug treatment in kidney transplant recipients. (2nd November 2021) - Georges, Coralie M. G.; Devresse, Arnaud; Ritscher, Sabrina; Wallemacq, Pierre; Toennes, Stefan W.; Kanaan, Nada; Persu, Alexandre
Abstract: Purpose: Hypertension is a common cardiovascular co-morbidity after kidney transplantation and contributes to shortened graft and patient survival outcomes. However, by contrast with adherence to immunosuppressive drugs, adherence to antihypertensive treatment in kidney transplant recipients has been seldom explored. The aim of the current study was to assess adherence to antihypertensive drugs in kidney transplant recipients from the Cliniques Universitaires Saint-Luc and to look for demographic and clinical characteristics associated with drug adherence. Methods: Demographic and clinical data were collected from medical files in a standardised case report form. Blood pressure was measured in the sitting position after 5 min rest, using validated oscillometric devices. Drug adherence was assessed by drug dosage in urine using liquid chromatography coupled with tandem mass spectrometry. Results: Our analysis included 53 kidney transplants recipients (75% of men, mean age: 57.2 ± 12.6 years, time since kidney transplantation: 9.5 ± 7.3 years, blood pressure: 130 ± 16/78 ± 11 mmHg on 2.1 ± 1.1 antihypertensive drugs). The proportion of patients showing full drug adherence, partial drug adherence, and total non-adherence to antihypertensive drugs was 79% ( N = 42), 15% ( N = 8), and 6% ( N = 3), respectively. Adherent patients did not differ from less or non- adherers in any of the analysed characteristics. Conclusion: The proportion of patients adhering to antihypertensive drug treatment among kidney transplant recipients appears similar to that reported for immunosuppressive drugs in renal transplanted patients (∼70%), but much higher than that observed in patients with drug-resistant hypertension (30–40%). Our results need further confirmation in a large, multicenter, prospective cohort.